Robot Assisted Radical Prostatectomy in A Patient with Previous Abdominoperineal Resection and Pelvic External Beam Radiation Therapy - Basatac, Cem; Akpinar, Haluk (Urology Journal, 2018)
Though previous major abdominal surgery and pelvic irradiation may be a significant drawback of subsequent laparoscopic procedure, technological advances such as better visualization and more controlled finer movements of robotic arms allowing better dissection in robotic-assisted laparoscopic surgery may reduce some of these challenges. However, limited data are available on the effect and safety of robotic surgery in these patients. The aim of this case report is to present efficacy and safety of robot assisted radical prostatectomy in a patient who has rectal and concurrent prostate cancer with the history of abdominoperineal resection, pelvic irradiation and adjuvant chemotherapy.